2017
DOI: 10.3311/ppci.11363
|View full text |Cite
|
Sign up to set email alerts
|

Durability Properties of Five Years Aged Lightweight Concretes Containing Rubber Aggregates

Abstract: Scrap tyres are one of the most important wastes. They can be used in different ways because of their availability and their non-degradable nature. This paper aims to demonstrate their reuse through durability properties experimental assessment of lightweight concretes aged five years, incorporating rubber aggregates as partial replacement of 5%, 7.5% and 10% of coarse/fine and coarse aggregates. The effect of the rubber aggregates on the lightweight concretes durability has been analysed. Firstly, the water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…The overuse of natural aggregate in the construction sector has harmed the environment in recent decades, and it is estimated that about 7.5 billion tonnes of aggregates are annually consumed by the concrete industry [1][2][3][4][5]. This environmental issue can be somewhat solved by partial replacement of natural aggregates with artificial lightweight aggregates in the building process [6][7][8][9][10]. Although the use of lightweight concrete (LC) dates back to the Roman Empire, modern age artificial lightweight aggregates were produced in the middle of the 20 th century and then they were developed by researchers in the concrete industry [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The overuse of natural aggregate in the construction sector has harmed the environment in recent decades, and it is estimated that about 7.5 billion tonnes of aggregates are annually consumed by the concrete industry [1][2][3][4][5]. This environmental issue can be somewhat solved by partial replacement of natural aggregates with artificial lightweight aggregates in the building process [6][7][8][9][10]. Although the use of lightweight concrete (LC) dates back to the Roman Empire, modern age artificial lightweight aggregates were produced in the middle of the 20 th century and then they were developed by researchers in the concrete industry [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nadine et al (Asroun, De Aguiar, Trouzine, & Medine, 2017) found out that the presence of CR increased the resistance of CR concrete to chloride acid attack. This is attributed to the stable chemical nature of the rubber particles that make them less reactive with the acid Figure 6.…”
Section: Chloride Permeability and Hydrochloric Acid Attackmentioning
confidence: 99%
“…However, this result does not agree with the findings of (Sabapathy et al, 2020) who reported that CR above 5% in rubberized GO modified ECC has insignificant effect on sulphate attack. In a research to assess the durability of 5 years aged lightweight concrete containing rubber aggregate was conducted by Nadine et al (Asroun et al, 2017). Their findings on sulfate attack revealed that the highest value for mass loss was recorded for 5% CR samples.…”
Section: Sulfate Resistencementioning
confidence: 99%
“…For each type of LWAC, different physical properties were tested as reference data for their potential practical applications. These tested properties include: strength (Cui et al, 2012a;Ilya et al, 2018;Medine et al, 2018), density (Lau et al, 2018), elasticity (Hilal et al, 2016), shrinkage (Alexandre Bogas et al, 2015;Rumšys et al, 2017), creep (Libre et al, 2011), thermal conductivity (Nguyen et al, 2017), abrasion resistance (Real and Bogas, 2017), and adsorption (Krc, 2015;Muñoz-Ruiperez et al, 2018). Although LWAC has its superiority in high strength and low density, LWAC has more obvious brittleness compared with other ordinary concretes, which can be partially attributed to its high strength (Beygi et al, 2014;Karamloo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%